Hubungan Tingkat Stres dengan Siklus Menstruasi Pada Remaja Putri Kelas 12 di SMA PGRI 1 Kota Bekasi - Ririn Khoerunnisa; Friska Junita; Rupdi Lumban Siantar (Universitas Malahayati Lampung, 2024)
ABSTRACT Stres in young women is caused because many young women experience severe and moderate stress and with short menstrual cycles. This study aims to determine the relationship between adolescent stres levels and the menstrual cycle at SMA PGRI 1 Bekasi City in 2023. This study aims to determine the relationship between adolescent stress levels and the menstrual cycle at SMA PGRI 1 Bekasi City in 2023. The method taken in by researchers, namely the type of quantitative research and observational analytic and with a cross-sectional design where in collecting data using questionnaires. The results showed that p-value of 0.001 or Sig 0.05 meaning that there was a relationship between stress levels and the menstrual cycle in grade 12 female adolescents at SMA PGRI 1 Bekasi City in 2023, with an OR(95% CI) value of 15.369 meaning that students who experienced stress has a risk of 15,369 times to experience abnormal menstrual cycles compared to female students who are not stressed.The conclusion from this study is that stress can affect the menstrual cycle. Keywords: Menstruation, Teenagers, Stres ABSTRAK Stres pada remaja putri disebabkan karena banyak remaja putri yang mengalami stres berat dan sedang serta dengan siklus menstruasi yang pendek. Penelitian ini bertujuan untuk Untuk mengetahui hubungan dari tingkat stres remaja dengan siklus menstruasi di SMA PGRI 1 Kota Bekasi Tahun 2023. Metode yang digunakan oleh peneliti yaitu jenis penelitian kuantitatif serta analitik observasional dan dengan desain cross sectional yang dimana dalam pengumpulan data menggunakan kuesioner. Hasil penelitian menunjukkan p-value sebesar 0,001 atau Sig 0,05 artinya ada hubungan antara tingkat stres dengan siklus menstruasi pada remaja putri kelas 12 di SMA PGRI 1 Kota Bekasi Tahun 2023, dengan nilai OR(95% CI) 15,369 artinya siswi yang mengalami stress berisiko 15,369 kali untuk mengalami siklus menstruasi yang tidak normal dibandingkan dengan siswi yang tidak stress. Kesimpulan dari penelitian ini yaitu stres dapat mempengaruhi siklus menstruasi. Kata Kunci: Menstruasi, Remaja, Stres